Peran Parental Structure terhadap Basic Need Satisfaction pada Siswa Kelas IV-VI di Sekolah Dasar â€œXâ€ Bandung - Yesika Nathasia Permadi; Jane Savitri; Destalya Anggrainy Mogot Pandin (Humanitas (Jurnal Psikologi), 2017)
Based on a study of 132 elementary school students in grade IV-VI found that there is significant parental structure effect on basic need satisfaction (R2 = 0,277, F = 49,704, and Ï = 0,000). Parental structure also has a significant influence on the three components of basic need satisfaction, namely need for autonomy (Ï = 0,000, F = 22,495), need for competence (Ï = 0,000, F = 45,106) and need for relatedness (Ï = 0,000, F = 21,091). Suggestions for research that will conduct further research are expected to undertake research on the influence of parental structures on basic need satisfaction using a wider coverage of respondents. In addition, the researcher proposes to the school to make a psychoeducation program with material related to the role of parental structures on the basic needs of satisfaction.